The Professional Development of Islamic Education Teachers: Enhancing Pedagogical Competence in the Digital Age - Eka Puji Srilestari (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
This study aims to investigate the professional development needs of Islamic Education teachers in enhancing their pedagogical competence in the digital age. Employing a qualitative approach with a case study design, data were collected through in-depth interviews and classroom observations of Islamic Education teachers in various urban schools. Thematic analysis revealed four major themes: the dual struggle of technological adaptation and value preservation, the gap between digital access and meaningful pedagogical integration, the transformative potential of collaborative learning communities such as the Subject Teacher Discussion Group (MGMP), and the emergence of a new professional identity as spiritual-digital facilitators. The findings indicate that Islamic Education teachers are not resistant to technology but are actively reflecting on how to integrate digital tools in ways that serve the holistic goals of Islamic education, including spiritual and character formation. The primary gap lies not in technical skills, but in the pedagogical wisdom to use technology contextually and in alignment with Islamic values. The study concludes that effective professional development must be sustained, collaborative, and specifically address the intersection of Islamic pedagogy and digital technology, recognizing teachers as the primary agents of educational transformation.